Food Safety and Risk - Rajkovic, Andreja; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: BioMed Central.)
The United Nations's second Sustainable Development Goal, Zero Hunger, aims to end world hunger by 2030. Access to safe food is imperative for achieving this goal. Food Safety and Risk is an open access, peer-reviewed journal that aims to contribute to this need by providing a multidisciplinary forum for all research dedicated to the perspective of risk assessment in promoting food safety, by encouraging more studies presenting risk/benefit analyses of scenarios impacting food safety. Areas such as biological, chemical, and physical hazards, food hygiene, water safety are included in the scope of the journal. It aims to create a forum welcoming all scientists whose research interests have relevance for food safety, including social, economic, and systemic approaches. Key topics of interest include: Risk/benefit assessments of food, nutrition and diets Biological, chemical, and physical hazards Drinking water safety Clean water for food production and food safety Emerging hazards Decontamination methods and applications Food preservation and storage Allergens and food safety Risk/benefit assessments of food from Genetically Modified Organisms Environmental and climate change effects on food safety Scientific studies analyzing the impact of migration, war, conflict, and extreme weather on food safety Food safety and risk in livelihoods and land ecosystems Food safety and risk in local and indigenous food systems Impact of food processing and manufacture (both established and novel methods) on food safety and health Novel methods for the detection of contaminants Toxicology of food contaminants Predictive models in food safety Risk management in food production and distribution.
Keywords: Food$1 (BSafety measures.s; Food$1 (BAnalysis.s; Chemistry; Food$1 (BMicrobiology.s; Food$1 (BAnalysis.s; Food science; Food Safety; Food Chemistry; Food Microbiology; Food Analysis; Food Science